Digital Natives and Civic Disengagement: Investigating the Role of Social Media Echo Chambers on Youth Political Apathy - John Ngirabong; Monica Kintomw; Timothy Rechab (Journal of Social Science Utilizing Technology, 2025)
Background. The growing prevalence of algorithmically curated social media environments has intensified concerns about youth civic disengagement, particularly among digital natives who rely heavily on online platforms for information and social interaction. Emerging scholarship suggests that echo chambers may limit exposure to diverse viewpoints, yet their specific influence on political apathy among young users remains insufficiently examined. Purpose. This study aims to investigate how social media echo chambers shape patterns of civic disengagement and attenuate political motivation among digital native populations. Method. A mixed-methods design was employed, combining a survey of 512 respondents aged 18–25 with in-depth interviews and digital trace analysis of users’ online interaction networks. Results. The findings indicate that strong echo chamber effects correlate with reduced interest in public affairs, lower perceived political efficacy, and diminished motivation to participate in offline or institutional civic activities. Interview data reveal that repetitive, ideologically homogeneous content fosters a sense of political fatigue and reinforces disengaged orientations. Conclusion. The study concludes that echo chambers contribute to youth political apathy not through coercive influence but through the gradual normalization of passivity and selective avoidance within digital cultures. These results underscore the need for media literacy interventions and platform-level design strategies that promote exposure to diverse political perspectives.